Eligibility for Minimally Invasive Coronary Artery Bypass: Examination of Epicardial Adipose Tissue Using Computed Tomography. Issue 2 (March 2017) - Dillon, Kate E. M.; Johnson, Marjorie; Chan, Ian L.; Kiaii, Bob
Abstract : Objective: A variable that necessitates conversion to a conventional full-sternotomy coronary artery bypass procedure from a robotic-assisted endoscopic single-vessel small thoracotomy is the inability to visualize the left anterior descending coronary artery within the surrounding epicardial adipose tissue using the endoscopic camera. The purpose of this study was to determine whether anatomical properties of the epicardial adipose tissue examined using preoperative computed tomography (CT) images are able to predict and thus reduce the need for intraoperative conversion based on effective preoperative exclusion criteria. Methods: Retrospective analysis of patient preoperative CT angiography scans from both converted (n = 17) and successful robotic-assisted (n = 17) procedures was performed. Where possible, measurements of epicardial adipose tissue were acquired from axial slices, at the most accessible segment of the left anterior descending coronary artery. Results: Results indicate that patients who successfully underwent the endoscopic single-vessel small thoracotomy procedure (mean ± SD depth, 4.9 ± 1.9 mm) had significantly less epicardial adipose tissue (38%, P = 0.002) overlying the vessel toward the lateral chest wall than those who were converted to the full-sternotomy approach intraoperatively (mean ± SD depth, 7.9 ± 3.2 mm). Using this as a retrospective exclusion criterion reduces the conversion rate for this group by 47%, while maintaining a high specificity (94%). No significant differences exist between the two groups with respect to the remaining epicardial adipose tissue measurements or body mass index. Conclusions: The addition of CT angiography measurements of the epicardial adipose tissue overlying the left anterior descending coronary artery may enhance preoperative surgical planning for this procedure, thereby reducing the instances of procedural changes.